Sistem Reservasi Web Laravel dan Algoritma FCFS pada Barbershop Rapioo - Dwi Purnomo; Arsito Ari Kuncoro Kuncoro; Budi Hartono (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
The issues observed at Barbershop Rapioo are quite evident in daily operations, where manual reservation and queue management often lead to disorganized service flow, unclear waiting times, and gradually declining customer satisfaction; in response to this, the study proposes a more structured solution through the development of a web-based reservation and queue management system built using the Laravel framework and supported by the First Come First Served (FCFS) algorithm, a simple yet effective approach that prioritizes customers based on arrival order and creates a sense of fairness that users can easily understand. The development process follows the System Development Life Cycle with a Waterfall approach, moving step by step from requirement analysis to system design, implementation, and testing, while data are gathered through direct observation, interviews with staff and customers, and documentation of service activities to ensure the system reflects real operational needs. The results indicate that the system successfully integrates reservation and queue processes into a single real-time platform, with functional testing showing a 100 percent success rate across all features, confirming its reliability, and usability evaluation using the System Usability Scale producing an average score of 82, which falls into the excellent category and suggests that the system is easy to use even for individuals with varying levels of technological familiarity. In practice, the impact is quite noticeable, as service efficiency improves, queue information becomes more transparent, and customers no longer experience uncertainty while waiting, making the system not only a technical solution but also a practical and relevant approach to enhancing service quality, particularly for small and medium-sized barbershop businesses.